Challenges and perspectives for the use of electric vehicles for last mile logistics of grocery e-commerce – Findings from case studies in Germany. (June 2021) - Ehrler, Verena Ch; Schöder, Dustin; Seidel, Saskia
Abstract: Purpose: More and more cities struggle to provide acceptable air quality and noise levels for their inhabitants. At the same time, urbanization is continuing, as is the need for supply with groceries in cities. Another ongoing trend is the growth of online shopping of groceries. Increase of online shopping in other areas, e.g. clothing, has resulted in augmented transport demand due to deliveries and returns. Therefore, an approach is needed to uncouple grocery supply related transport demand from emissions augmentation. This is only possible though, if transportation efficiency is further improved and if lower emission technologies (noise and fumes) are applied, e.g. electric vehicles. With limited data available on urban commercial transport as well as on e-mobility, it is difficult for both logistics providers and politics to prepare for these developments and understand their implications. Focusing on the German market and using the test case of a renowned logistics service provider who trialed e-vehicles for commercial transport, this paper discusses potential shifts in grocery shopping habits, maps out perspectives, prerequisites and challenges for a shift to electric vehicles for their distribution and derives recommendations for industry and politics based on the findings. Research approach: The data basis of the research is as follows: Whereas the analysis of online grocery shopping had to be based mainly on secondary data, analysis of the potential and prerequisites for the use of electric vehicles for their distribution are based on real-life test cases. This is due to the fact that primary data on commercial transport and on logistics structures of groceries in particular is difficult to obtain in general, and especially in Germany. This is due to the tight data protection in Germany, not allowing to trace employees unless union representatives and employees have agreed. Furthermore, businesses do not want to disclose their logistics structures. The real-life test cases of electric vehicles for grocery deliveries were piloted by Hellmann Worldwide Logistics in Germany and were accompanied by the researchers. The synthesis of the insights gained build the basis for a discussion, whether e-mobility is the right approach to cope with the impact of the trends of urbanization and online grocery shopping and which further developments are needed for reducing grocery-logistics related emissions. Findings: The analysis reflects the following aspects and findings: status-quo and trends of online groceries sales in Germany motivation for and experiences made within a real-life test case of use of electric vehicles by a renown logistics service provider in Germany implications from the findings of the test cases and their relation to online grocery sales identification of perspectives, prerequisites and challenges for the successful introduction of electric vehicles for the distribution of online sales, in particular online grocery sales Research impact: Limitations experienced during the research and challenges encountered build the basis for the identification of further research fields needed in order to be able to develop and conceive sustainable urban logistics concepts. Practical impact: Findings are included in the logistics service provider's involved endeavors to further reduce their emissions. In particular, in the context of an upcoming trial phase for innovative urban distribution structures in Bremen, Germany. Highlights: Trend analysis of the emerging market of e-groceries in Germany. Analysis of a real-life test case of electric vehicles for grocery logistics in Germany. Prerequisites and perspectives for a successful introduction of electric vehicles for urban distribution of online sales.